Pemberdayaan Kader Posyandu Lansia dalam Deteksi Dini Risiko dan Pencegahan Depresi pada Lanjut Usia di Desa Penyengat Olak Muaro Jambi - Daryanto Daryanto; Mila Triana Sari (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
According to the World Health Organization (WHO), Depression disorder ranks second in the burden of disease in the world in 2020. Data from Riskesdas, the prevalence of depression in Indonesia is 6.1 per mile and only 9% are undergoing medical treatment. Depression prevalence in Jambi 1.8 per mile. As many as 40% of people with depression have suicidal ideation, and about 15% are successful at it. The purpose of the implementation of this community service activity is to increase community participation, especially for elderly posyandu cadres in early detection of risks and symptoms and prevention of depression in advanced , simulation, pre and post test, with the target of cadres at the post Yandu elderly, amounting to 30 people. The outcome of this community service activity is the empowerment of cadres about depression, the risk of depression, early detection and prevention of depression. The results obtained are that the understanding of cadres has increased from an average value of 52.8 to 81.8 regarding detection of risk factors and symptoms and prevention of depression in the elderly. and symptoms and prevention of depression. Conclusion: Community service activities provide benefits to increase cadres understanding and increase cadre participation in early detection of risks and symptoms and prevention of depression. Health cadres are expected to carry out further screening of all elderly people in their area so that further action can be taken in order to meet the welfare of the elderly